Estimation of the prevalence of tobacco consumption among rural women in South India using mixed methods analysis - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
Background: Tobacco consumption is a public health problem in Tamil Nadu. Objectives: The current study was done to estimate the prevalence of tobacco consumption among rural women and to identify the sociodemographic characteristics with high prevalence of tobacco consumption. Materials and Methods: It was a community-based cross-sectional descriptive study conducted among women ≥18 years of age. Mixed methods were employed to obtain the comprehensive picture about the substance use among women. Multistage random sampling method was used to interview 210 women using a semi-structured and pretested schedule. This was followed by key informant interviews, in which nine women were interviewed. Frequency distributions and Chi-square test were employed to study the association. In addition, manual content analysis was done to identify the reasons for the initiation of tobacco consumption and the measures to curb the practice. Results: The prevalence of tobacco consumption among the women was estimated as 15.2%. Women in the lower socioeconomic status group showed a higher prevalence of tobacco consumption than the middle and high socioeconomic status group. All 32 (100%) women were consuming tobacco products in the smokeless forms. Further, 28 (87.5%) women were not willing to quit tobacco consumption. Conclusion: The prevalence of tobacco consumption among the women was estimated to be above expectation of the national figures. Lower socioeconomic class and poor educational status were found to be major determinants for tobacco consumption among rural women.